Evaluation of Vocational High School Dual System Education (DSE) in Improving the Competitiveness of Manpower in the Manufacturing Industry Sector in East Java Province - Rizqi Qurniawan (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2020)
The increase in Indonesia’s competitiveness ranking in 2018 is one indicator of improving the quality of industry and vocational education in Indonesia. However, the quality of the Indonesian workforce is still not good enough, even declining. The Dual System Education Program at the Vocational High School level is an important factor in solving unemployment problems and improving the quality and competitiveness of human resources in Indonesia. This study uses the correlation of the DSE cost index with the competitiveness index of the manufacturing industry in the provinces of Indonesia. The significant positive correlation between the two variables indicates that an increase in the budget for training and certification costs in Dual System Education in Vocational High Schools will increase business competitiveness in the manufacturing industry sector. In addition, this study also looks at the correlation between the DSE cost index and the open unemployment rate for vocational high school graduates in East Java Province. Both variables show a negative correlation, but not significant. This means that the dual system education budget does not significantly affect the open unemployment rate for vocational high school graduates between districts/cities in East Java Province. Improvements in budget allocations, training, apprenticeship systems, certification, curriculum, and collaboration with the business world in the Dual System Education system (DSE) of Vocational High Schools in East Java Province are expected to be able to make vocational education graduates have competencies that are in line with market demand and are ready to work. work so as to increase the competitiveness of the manufacturing industry.